CRISPR/Cas9 Genome Editing To Demonstrate the Contribution of Cyp51A Gly138Ser to Azole Resistance in Aspergillus fumigatus - Umeyama, Takashi; Hayashi, Yuta; Shimosaka, Hisaki; Inukai, Tatsuya; Yamagoe, Satoshi; Takatsuka, Shogo; Hoshino, Yasutaka; Nagi, Minoru; Nakamura, Shigeki; Kamei, Katsuhiko; Ogawa, Kenji; Miyazaki, Yoshitsugu (Antimicrobial agents and chemotherapy, 2018)
A pan-azole-resistant Aspergillus fumigatus strain with the cyp51A mutations Gly138Ser and Asn248Lys was isolated from a patient receiving long-term voriconazole treatment. PCR fragments containing cyp51A with the mutations were introduced along with the Cas9 protein and single guide RNA into the azole-resistant/susceptible strains. A pan-azole-resistant Aspergillus fumigatus strain with the cyp51A mutations Gly138Ser and Asn248Lys was isolated from a patient receiving long-term voriconazole treatment. PCR fragments containing cyp51A with the mutations were introduced along with the Cas9 protein and single guide RNA into the azole-resistant/susceptible strains. Recombinant strains showed increased susceptibility via the replacement of Ser138 by glycine. Genetic recombination, which has been hampered thus far in clinical isolates, can now be achieved using CRISPR/Cas9 genome editing.